Exploring the Tribological Potential of Y2BaCuO5 Precursor Powders as a Novel Lubricant Additive - Shuo Cheng; Longgui He; Jimin Xu (Lubricants, 2025)
Friction leads to substantial energy losses and wear in mechanical systems. This study explores the tribological potential of the high-temperature superconductor precursor Y2BaCuO5 (Y211), synthesized via chemical co-precipitation, as a novel additive to PAO6 base oil. A 0.3 wt.% Y211/PAO6 lubricant (CD) was formulated using ultrasonic dispersion. Tribological performance was evaluated using a custom end-face tribometer (steel-on-iron) under varying loads (100–500 N) and speeds (300–500 rpm), comparing CD to neat PAO6. The results indicate that the Y211 additive consistently reduced the coefficient of friction (COF) relative to neat PAO6, maintaining a stable value around ~0.1. However, its effectiveness was strongly load-dependent: a significant friction reduction was observed at 100 N, while the benefit diminished at higher loads (>200 N), with the COF peaking around 200 N. Rotational speed exerted minimal influence. Compared with neat PAO6, the inclusion of 0.3 wt.% Y211 resulted in a reduction in the coefficient of friction by approximately 50% under low-load conditions (100 N), with COF values decreasing from 0.1 to 0.045. Wear depth measurements also revealed a reduction of over 30%, supporting the additive’s anti-wear efficacy. Y211 demonstrates potential as a friction-reducing additive, particularly under low loads, but its high-load performance limitations warrant further optimization and mechanistic studies. This highlights a novel tribological application for Y211. The objective of this study is to evaluate the tribological effectiveness of Y2BaCuO5 (Y211) as a lubricant additive, investigate its load-dependent friction behavior, and explore its feasibility as a multifunctional additive leveraging its superconductive precursor structure.